Winx Club - Straffi, Iginio (USA, 4 Kids Entertainment, 2004)
In a magical universe, witches, warriors begin fighting in the name of good .vs. evil! A group of five teenaged girls where choosen to defend the universe with their magical powers. They're smart, They're stylish and they are magical fairies, They are the Winx Club! The Winx Club must defend their universe from having it be turned into darkness and terror by the Senior Witches. The magic is in you on the Winx Club.
In a magical universe, witches, warriors begin fighting in the name of good .vs. evil! At a magic school, five teenage girls are selected to defend the universe with their magic.
Barton Bishop
Language(s): Turkish Subtitle(s): No Subtitle
Keywords: Action; Adventure; Animation -- Tv Series